Involvement of p38 MAPK and MAPKAPK2 in promoting cell death and the inflammatory response to ischemic stress associated with necrotic glioblastoma - Soo Yeon Kim; Miaolu Tang; Stephen Y. Chih; Jessica Sallavanti; Yan Gao; Zhiqiang Qiu; Hong-Gang Wang; Wei Li (Cell Death and Disease)
Abstract The association of necrosis in tumors with poor prognosis implies a potential tumor-promoting role. However, the mechanisms underlying cell death in this context and how damaged tissue contributes to tumor progression remain unclear. Here, we identified p38 mitogen-activated protein kinases (p38 MAPK, a.k.a. p38) as a key player in promoting cell death and the inflammatory response to ischemic stress associated with necrotic tumors. We found that glioblastoma (GBM) cells expressing patient-derived Kirsten rat sarcoma (KRAS) or phosphoinositide-3-kinase (PI3K) active mutants showed enhanced cell death under ischemia-mimetic conditions in vitro and were more likely to develop into necrotic tumors in vivo. Cell death in both settings depended on p38, which is also required for tumor progression driven by KRAS or PI3K. Under ischemia-mimetic conditions, GBM cells undergo reactive oxygen species (ROS)-dependent cell death. Gene expression in these cells recapitulated multiple features observed in peri-necrotic tumors from patient GBM. Further studies showed the involvement of a positive feedback loop between the p38-MAPK-activated protein kinase 2 (MAPKAPK2, a.k.a. MK2) signaling axis and the unfolded protein response signaling components activating transcription factor 4 (ATF4) and inositol-requiring enzyme 1 (IRE1α) in driving ischemic tumor cell death. This signaling cascade was further potentiated by RAS or PI3K activation under ischemic conditions, contributing to the inflammatory gene expression response. Therefore, our study suggests that p38 could be targeted to relieve the inflammatory response in necrotic tumors and inhibit GBM progression.